UN peacekeeping in Mali: Time to adjust Minusma's mandate - Denis Tull (Stiftung Wissenschaft und Politik (SWP), 2019)
The mandate of the United Nations Multidimensional Integrated Stabilization Mission in Mali (Minusma) ends on 30 June 2019. There is little doubt that the UN Security Council will extend the mission. Less clear is how Minusma contributes to Mali's stabilisation and how the mandate could be altered to increase the mission's effectiveness. In light of changing conditions in Mali, the Security Council should consider a stronger Minusma engagement in central Mali. But for this to happen, cuts must be made in the north.
Keywords: 320